2002
DOI: 10.1053/ajcd.2002.36636
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Methodology of Evaluation for Latex Allergy Among Allergists in the United States: Results of a Cross-Sectional Survey

Abstract: Almost all responding allergists evaluated patients for latex allergy, with approximately two thirds utilizing prick testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, an FDA‐approved NRL skin test reagent is not commercially available in the United States [27, 48]. As a consequence, most allergists (64%) utilize NAL‐specific IgE serology as the initial test in the evaluation of NRL allergy [49]. US FDA‐cleared serological assays for NRL‐specific IgE are readily available.…”
Section: Discussionmentioning
confidence: 99%
“…However, an FDA‐approved NRL skin test reagent is not commercially available in the United States [27, 48]. As a consequence, most allergists (64%) utilize NAL‐specific IgE serology as the initial test in the evaluation of NRL allergy [49]. US FDA‐cleared serological assays for NRL‐specific IgE are readily available.…”
Section: Discussionmentioning
confidence: 99%
“…Prick testing, as with glove challenge, is known to have the potential to cause anaphylactic reactions (4). In a survey of allergists in the USA, 6% of respondents reported episodes of anaphylaxis in patients undergoing latex allergy testing, most of these from using a homemade solution or while performing a use test (5). 17% of the investigators in this survey indicated that they are not willing to perform prick testing or glove challenge because of this risk or because of lack of equipment or staff, thereby relying for diagnosis on the less‐sensitive measurement of latex‐specific IgE (6).…”
Section: Discussionmentioning
confidence: 99%